Tingkat Religius dengan Kecemasan Menghadapi Ujian Akhir Semester (UAS) Kelas 8 SMPN 12 Kota Bekasi - Intan Cahnia; Halimatussadiyah; Fitri Nur Raihana; Irma Nurul Halimah; Rachmitha Widiya Rochman; Muhalisah Muhalisah; Yayat Suharyat (BADAN PENERBIT STIEPARI PRESS, 2023)
Anxiety is common in everyone, especially in school students when it comes to the implementation of exams, this is indicated by some behaviors as a response to anxiety. The purpose of this study was to determine the level of anxiety in grade 8 students of SMPN 12 Kota Bekasi when approaching the final semester exam. The research was designed using quantitative methods with a correlational approach. The subjects of the study were grade 8 students of SMPN 12 Bekasi City. Data collection using questionnaires through google from. Meanwhile, data analysis uses the t test and the f test. The results showed that the regression equation of student anxiety variables was 53,078. The figure indicates that the null hypothesis (Ho) is rejected which says there is no influence of religious level with student anxiety, meaning that each student is confirmed to have anxiety, only the level of anxiety varies. The implications of this study suggest that each school can deepen and strengthen students' religious competence so that anxiety levels are not at high levels. Low anxiety can motivate children to learn. During the test, people who felt confident performed better than those who felt less anxious. Excessive worry can also weaken students' learning abilities. Decreased confidence of students during exams can affect their learning. Because religiosity or diversity refers to how deeply understood or practiced religious teachings in daily life, prayer becomes very important before each exam in the final semester.